Analysis of Telunjuk Sakti service Risk Management as Quick Win Smart Governance Wonogiri Regency - Singgih Manggalou; Binti Azizatun Nafi’ah (Universitas Medan Area, 2023)
Program implementation in local government is not easy (Musa, 2010). Many challenges must be faced in order to minimize program failures, including the Telunjuk Sakti service program. This program is a mainstay service program for Wonogiri Regency in the current smart city era. So there is a need for risk management to analyze the possible risks that arise as a result of the program (Bhatta, 2008). This study uses a qualitative method. The purpose of this study was to analyze risk management for the Telunjuk Sakti service as a quick win smart governance in Wonogiri Regency. By understanding the risks posed by this program, risk mitigation can minimize unwanted impacts. This encourages the smooth running of the Telunjuk Sakti service index program as a quick win from smart governance in Wonogiri Regency. Researchers found that people's low literacy of the program is an extreme risk. These social risks arise as a result of the majority of the population of Wonogiri Regency being rural and untouched by technology. Technical matters become a high risk, such as the absence of data backup at the village level, HR competence in handling applications and access to wifi and FO being interrupted at any time. This technical matter can hinder the running of the service program, so strengthen the anticipation of technical issues by building DRC/cloud, HR training, and alternative LAN networks.